Pengaruh Struktur Modal, Pertumbuhan Laba, Kualitas Audit dan Ukuran Perusahaan Terhadap Kualitas Laba - Anggarani, Vera; Yudi, Yudi; Rahayu, Rahayu (Jurnal Akuntansi & Keuangan Unja, 2025)
The purpose of this study was to determine the effect of Capital Structure, Earnings Growth, Audit Quality and Company Size on Earnings Quality, in automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. This study uses purposive sampling technique in determining the research sample used, where this research technique is based on predetermined criteria. The sample in this study was 60 samples from 12 companies multiplied by the observation year, namely 5 years. The data used is secondary data. The analysis method used is Multiple Linear Regression using SPSS 26 (for windows) software. The results showed that Capital Structure, Earnings Growth, Audit Quality, and Company Size simultaneously have a positive effect on earnings quality; Capital Structure has no effect on earnings quality; Earnings Growth affects earnings quality; Audit Quality has no effect on earnings quality; and Company Size has no effect on earnings quality.